The Role of Schools in Shaping Childrens Islamic Character through the PPM KI Program at SB At-Tanzil Serdang - Nadya, Nabila Nurul; Hala, Sarah Rofiqa M.; Limehu, Khairun Nisa; Handayani, Trikinasih; Kurniaji, Ganno Tribuana (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
In order to develop Islamic character through cooperation and brotherhood, the Community Service Program (PPM) becomes an effective approach. PPM involves collaboration between schools and external partners, in this case, International Partnerships (KI), to improve the quality of education and the formation of Islamic character. Within the framework of cooperation with KI, schools can adopt best practices from international educational institutions and implement them in the school environment. Through various activities and learning, schools can create opportunities for children to interact, cooperate, and build brotherhood with their peers. Through this process, children can learn to respect, support, and understand each other, as well as develop inclusive and caring attitudes. This research will use qualitative research methods with a case study approach. This method will allow researchers to gain a deep understanding of the role of schools in shaping the Islamic character of children, with a focus on cooperation and brotherhood in the school environment.